The Influence of Animation Videos on Expressive Language Skills in Preschool Kobar Anugerah, Batujala Village, Bontoramba District, Jeneponto Regency - M, Syamsidar.; Herlina, Herlina; Musi, Muhammad Akil (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This research aims to: 1) find out what the effect is after being given an animated video at the Kobar Anugrah Early Childhood Education in Batujala Village. 2) To find out what the influence was before being given an animated video at the Kobar Anugrah Early Childhood Education in Batujal Village. 3) To find out whether there is an influence of learning videos in Kobar Anugrah Early Childhood Education in Batujala Village. This research is a quantitative descriptive research by describing variables that support the data in the form of numbers generated from the actual situation. This research uses primary data which collects data using questionnaires and interviews. The researcher uses quantitative analysis, multiple linear regression analysis and analysis of the coefficient of determination. with the help of SPSS17. The population in this study was 47 early childhood children at the Kobar Anugrah Early Childhood Education School, Batujala Village, carried out on May 15 2023 at Kobar early childhood education in Batujala Village, Bontoramba District, Jeneponto Regency, South Sulawesi Province. The results of the research obtained using the Animated videos have the effect of helping young children be active in expressive language at early childhood education schools in Kobar, and teachers are also more active in the early childhood education learning process using animated digital media learning methods. And master digital media materials with animated video materials.